Integration in the Czech Republic as Seen from the Perspectives of Intercultural Workers - Konopíková, Michaela; Krajewska, Aleksandra (My University, 2024)
This text focuses on aspects of the integration of immigrants from the perspective of intercultural workers. The qualitative research explored how intercultural workers in the Czech Republic perceive and understand integration, with special emphasis on their interpretation of what makes a successfully integrated immigrant. Our conclusions indicate the predominance of a dualistic view of integration based on the acquisition of Czech language skills and the achievement of self-sufficiency. The culturally determined behavior of immigrants can significantly influence their cooperation with the majority society in areas such as education and their orientation in the social system. This research contributes to understanding the integration of immigrants and reveals a complex interplay of language, self-reliance, cultural prejudices, and the role of intercultural workers in facilitating mutual understanding between new arrivals and the majority population.
Integrace v České republice z pohledu interkulturních pracovníků
Keywords: integration, intercultural work, intercultural communication; integrace, interkulturní práce, interkulturní komunikace